Geographical origin traceability of kiwifruit products using stable isotope and multi-element analysis with multivariate modeling: Feature extraction, selection of model and variable, and discrimination - Wang Shuanhui; Chen Chang; Tian Jing; Liu Zhi; Mei Xianxian; Zhou Jialu; Wang Dongguang; Zhu Shaohua (Food Chemistry: X)
The mislabeling of kiwifruit origin frequently disturbs market competition and governmental supervision, significantly undermines brand reputation and consumer rights. In this work, a total of 370 kiwifruits from 8 different countries in global were collected, and 6 stable isotope ratios (SIRs), 10 mineral elements (MEs), and 16 rare earth elements (REEs) were determined for origin traceability study. One-way analysis of variance (ANOVA) showed that regional differences of 32 variables are at significant level (P value =0.00). Supervised methods, partial least squares-discriminant analysis (PLS-DA) and its derivative algorithm (OPLS-DA), linear discriminant analysis (LDA), enhanced identification performance and finally elevated the accuracies to 100 % for all kiwifruit origins. Lu, Tb, Eu, Ho, Pm, Y, δ34S, δ2H, δ15N, Mg, Se were main contributive variables for LDA modeling (AUC value >0.5). A blind test was conducted using 63 samples randomly selected from Chinese market. The predicted result indicated a significantly high probability of origin mislabeling of imported kiwifruit products, with percentages ranging from 30.0 % to 90.0 %. This study may provide technical supports for combating origin mislabeling conduct, and ensuring food authenticity of kiwifruit in global trade.